Risiko Bank, Struktur Kepemilikan dan Ukuran Bank terhadap Kinerja Keuangan pada Perusahaan Perbankan periode 2020-2022 - Henwie Henwie (IPM2KPE, 2024)
This research aims to analyze the impact of bank risk, ownership structure and bank size on the financial performance of banking companies. Evaluation of financial performance using profitability ratio analysis is the main method for assessing financial management efficiency. Risks are identified as potential losses or harm that can be predicted in advance with relevant data. Differences in ownership structure impact the policies taken, while company size results in different business risks. This research adopted a quantitative approach with a sample of 28 respondents selected through purposive sampling. Data analysis was carried out using multiple linear regression. The research results show that bank risk has a negative and significant effect on financial performance, while ownership structure has a negative but not significant effect. On the other hand, bank size has a positive and significant influence on financial performance. Overall, bank risk, ownership structure and bank size simultaneously have a positive and significant impact on financial performance. In conclusion, this research provides a deeper understanding of the factors that influence the financial performance of banking companies. Keywords: Financial Performance, Bank Risk, Ownership Structure, Bank Size